Semiárido, mudanças climáticas e segurança alimentar e nutricional: um olhar sobre o rural pesqueiro da comunidade quilombola Bela Vista do Piató - Assu, RN - Silva, Louyse Rodrigues da (2023)
The Bela Vista Piató quilombola community located in the municipality of Assú/RN, semi-arid region of Rio Grande do Norte, has faced challenges with climate and socio-environmental issues that threaten economic activities, in addition to changing dynamics and productive relationships, directly affecting food production. In this sense, the objective of this study was to analyze the Food and Nutritional (In)Security (FNS) of residents of the quilombola community Bela Vista Piató and reflect on the relationship with socio-environmental issues and the impacts of climate change in Lagoa do Piató in Assú/ RN, which has historically been a place of food production. The research was phased, in addition to the theoretical framework constructed from analytical categories such as: semiarid, climate change, food and nutritional security, rural and artisanal fishing communities, a case study was made possible. The methodology consisted of participant observation at meetings of the Quilombola Community Association of Bela Vista Piató, in exploratory interviews, aiming to understand the residents' perception of environmental issues and possible climate associations. In relation to the food consumption of residents, questionnaires were applied, including aspects about the perception of residents and questions to directly measure food and nutritional security in the dimension of regular and permanent access to food for the population, through a call Brazilian Food Insecurity Scale (EBIA). Finally, in the analyses, it was associated with climate projections for the region and the food consumption of the studied community from an interdisciplinary and qualitative perspective. There was a prevalence of 96.1% of residents interviewed in a situation of food insecurity: of the individuals who lived in a situation of food insecurity, 46.07% were fishermen and 47.05% were farmers. Regarding residents' perception of climate change, 77.45% perceive it when relating the difficulties in performing their functions as a result of the changes. A prevalence of food insecurity of 73.52% is observed in households headed by quilombola women. It is concluded, therefore, that the population is food insecure and climate change has connections resulting in severe impacts on the four dimensions of the local population's SAN.